Lasibidoupins A and B, two new compounds from the stems of Lasianthus bidoupensis V.S. Dang & Naiki. Issue 3 (1st February 2023) - Pham, Nguyen Kim Tuyen; Nguyen, Thi Diem Huong; Nguyen, Thi Mong Cam; Nguyen, Gia Dinh; Huynh, Cong Doan; Vo, Thi Nga; Nguyen, Thi Quynh Trang; Duong, Thuc Huy; Dang, Van Son; Huynh, Bui Linh Chi; Tran, Thi Ngoc Mai; Nguyen, Tan Phat
Abstract: From the Lasianthus bidoupensis stems, two new compounds, including one new 9, 10-anthraquinone, lasibidoupin A (1 ), and one new 6, 7-benzocoumarin, lasibidoupin B (2 ), together with one known compound, 11- O -methyldamnacanthol (3 ) were isolated using chromatographic method. Their structures were determined by extensive HRMS, and NMR assignments. Compound 3 was reported for the first time from this species. New compounds (1 & 2 ) were tested for the cytotoxicity against three human cancer cell lines (MCF-7, HeLa, and NCI-H460) by SRB assay. As results, 1 & 2 exhibited significant cytotoxic activity against all cancer cell lines (IC50 ranged from 0.058  ± 0.003 to 0.177 ± 0.014 μM). Graphical Abstract: UF0001